ANALISIS PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA NONGKOSAWIT KOTA SEMARANG - Impiansari, Yohana Amalia; S., Endang Larasati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Public participation is the people involvement in the decision making, problem identification and the evaluation process in their own region. Village resort is a certain region that has its own unique appeals and the potential to become a tourist attraction based on the its culture and its nature in order developing the region and the people's standard of living. The purpose of this research is to observe and identify the public involvement and the factors that affect the public participation in order to develope Nongkosawit village resort. This research is using descriptive narrative with a qualitative approach method. The data collection method is using observational study, interview, survey data study, and scientific data study. The result shown the Nongkosawit villagers participation in the development of village resort project is merely a pseudo participation. The level of public participation is only a delegated power. A big factors that boost the public participation is gender, education, culture and some external factors, whereas the factors that hinder the public participation is the people's occupation, and poeple's knowlegde about the project and external cultural distrust. It is advised to improve the participation by educating the people itself about the project and engage them to join the worker union so they can maximalize the contribution and involvement by debriefing, educating, and training Nongkosawit villagers in order to increase people's knowlegde about the project.